Preparation of cross-linked carboxymethyl jackfruit starch and evaluation as a tablet disintegrant - Nisit Kittipongpatana (2018)
The main purposes of this study are to prepare cross-linked carboxymethyl jackfruit starch (CL-CMJF) and to evaluate its pharmaceutical property as a tablet disintegrant. CL-CMJF was prepared by a dual carboxymethylcrosslinking reaction in a flask containing jackfruit seed starch (JFS), chloroacetic acid (CAA), sodium hydroxide (NaOH) and sodium trimetaphosphate (STMP). The reaction was carried out using methanol as a solvent for 60 min at 70° C and at JFS:CAA:NaOH:STMP ratio of 1.0:0.29:0.28:0.07. The obtained CL-CMJF, with degree of substitution and degree of crosslinking calculated to be 0.34 and 0.06, respectively, was insoluble but swellable in water. Rheological study revealed a decreased in solution viscosity compared to the non-crosslinked CMJF. The water uptake of CL-CMJF was 23 times higher than that of native starch and was comparable to that of a commercial superdisintegrant, sodium starch glycolate (SSG). The swelling ability of CL-CMRS was similar to that of crosscarmellose sodium (CCS), another commercial superdisintegrant. Disintegration test of aspirin tablets containing 2%w/w of JFS, CL-CMJF, SSG and CCS showed disintegration times in the order of SSG < CCS ∼ CL-CMJF ⋘ JFS. The results suggested that CL-CMJF could be developed as a tablet disintegrant.